KAJIAN AL-QUR’AN TENTANG TAJHIZUL JANAZAH ERA PANDEMI COVID-19 DI MASYARAKAT - Mujiburrahman Mujiburrahman; Umar faruq (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2021)
This article has been discussed about the study of the Qur'an on tajhizul Jenazah which is attacked by COVID-19 virus. The analysis of this article is the Qur'an’s verses that have been discussed about the tajhizul Jenazah. The method used by the author is conceptual thematic; the author collects data of the sourced from the Qur'an (primary) related to tajhizul Jenazah that occurred in the community during the covid-19 pandemic, as well as referring to books used as literature related to the theme of discussion. Allah Swt said about His respect to Adam and His noble who is given to thim, dnd mentions that He created them in the best form. Islamic rules regarding tajhizul Jenazah show that Islam greatly glorifies mankind, not only when its lifetime, when it has died, jenazah must be treated properly. Tajhizul Jenazah is one of the fiqh studies that must be quasi by the younger generation so that it is formed in the current of globalization era that can still increase the knowledge and can be applied in society.